OGG1S326C variant frequent in human populations facilitates inflammatory responses due to its extended interaction with DNA substrate - Jinling Han; Meichen Zhang; Jiakun Ge; Zhihua Ji; Jianyi Zhao; Yinchao Hu; Chunshuang Li; Yaoyao Xue; Xining Li; Haiwang Zhao; Zixu Cui; Miaomiao Tian; et al. (Proceedings of the National Academy of Sciences, 2025)
8-oxoguanine (8-oxoGua) is one of the most frequent forms of oxidative DNA base lesions, repaired by 8-oxoguanine DNA glycosylase 1 (OGG1) via base excision repair (BER) pathway to maintain genome fidelity. The human allelic variant hOGG1 S326C , prevalent in Caucasians and Asians, has been regarded as a susceptibility factor for various diseases, yet its pathogenic mechanism remains elusive. In this study, we demonstrate that Ogg1 S326C/S326C mice exhibit increased and sustained airway inflammation compared with wild-type (WT) Ogg1 S326/S326 mice. Mechanistically, in response to inflammatory stimulation, OGG1S326C undergoes reactive oxygen species-induced dimerization, which impairs its base excision function, but prolongs its association with promoter-embedded substrate(s), leading to an increase in NF-κB’ DNA occupancy, subsequently the excessive expression of proinflammatory cytokines and chemokines, and the exacerbated lung inflammation. In contrast, Serine at position 326 in WT -OGG1 is constitutively phosphorylated by CDK4. To fulfill the requirement for its function in transcriptional regulation, the phosphorylated OGG1 needs to undergo dephosphorylation to rescue DNA binding ability. In this scenario, OGG1S326C lacks this phosphorylation site, disrupting this regulatory cycle. Notably, administration of a small molecule inhibitor of OGG1 prevents OGG1S326C from binding to DNA and significantly decreases gene expression and inflammatory responses. Our findings elucidate a molecular basis for the increased disease susceptibility of individuals carrying the hOGG1 S326C variant and propose the therapeutic potential of OGG1 inhibitors in mitigating inflammation-driven pathologies.